PS-014 Safety analysis of ledipasvir/sofosbuvir, with or without ribavirin, in patients with chronic hepatitis C virus infection: Adverse events and drug interactions. (14th February 2016) - Pragosa, A; Nunes, C; Elias, C; Soares, J; Fernandes, J; Oliveira, MJ; Frade, P; Afonso, R; Gonçalves, S
Abstract : Background: New antiviral drugs used in hepatitis C treatment show better efficacy and safety. However, their adverse events (AEs) and interaction (IT) profiles require careful review of all concomitant therapy and patient education. As medication experts and due to their privileged access to patients, hospital pharmacists can monitor concomitant therapy as well as AE incidences, preventing potential risks and contributing to a reduction in morbidity and mortality associated with treatment. Purpose: Analysis of AE incidences and IT, with concomitant therapy, of ledipasvir/sofosbuvir (LDV/SOF), with or without ribavirin (RBV), in patients with chronic hepatitis C virus infection treated at Hospital Prof Doutor Fernando Fonseca (HFF). Material and methods: In January 2015, we began a prospective study in patients receiving LDV/SOF, with or without RBV. At every visit to the HFF ambulatory pharmacy department, patients were interviewed during their pharmaceutical appointment and all AEs were identified as well as all concomitant therapy. Patients rated the AEs as mild, moderate or severe. IT profile was evaluated at Micromedex and hepdruginteractions.org. Clinical records were also considered (Soarian, Siemens). Data were analysed in Excel, Microsoft and will be collected until January 2016. Results: Of all 107 patients presently under therapy, 44% were polymedicated. Among those, 79% had drug-drug IT potential and maintained treatment after clinical review and 21% had changes in concomitant therapy. IT with sporadic therapy was also detected in 15% of patients. Treatment related AEs occurred in 73% of all patients. Among patients receiving LDV/SOF, 53% had AEs not described in the Summary of Product Characteristics, namely visual disturbances (26%), nausea (14%), asthenia (8%), dizziness, insomnia, loss of appetites and abdominal pain (6%). In patients receiving RBV, 8% confirmed appetite increase. Among all non-described AEs, 16% were rated as severe. Conclusion: Polymedication is a potential risk to ITs which will have a negative impact on efficacy and safety treatment outcomes. To date, among 210 pharmacy appointments, there were 62 (30%) interventions, all of them accepted. Active pharmacovigilance will allow pharmacists to act immediately on problem recognition. References and/or Acknowledgements: Alqahtani, et al . Safety and tolerability ledipasvir/sofosbuvir with and without ribavirin in patients with chronic hepatitis C virus genotype 1 infection: Analysis of phase III ION trials. Hepatology 2015:6:25-30 No conflict of interest.